Intervenir sur l'aphasie en contexte hospitalier : analyse des pratiques de rééducation et d'évaluation - Merlino, Sara (My University, 2017)
In this paper, we analyse post-stroke aphasia speech therapy sessions taking place in the hospital setting. During the acute phase of the pathology, the objective of the session is both to give a first recovery to the patient and to evaluate the troubles issued from the stroke lesion. Using an interactional perspective, we analyse the interactive organization of different tasks performed during these sessions and show the methodical practices and resources used by the participants to accomplish them. This allows us to reflect not only on how tasks are locally and interactively realized, but also on how they affect the type of engagement exhibited by the patient and the visibility of his/her different heterogeneous competences. We finally discuss the impact this can have on the assessment of the patient's residual linguistic and cognitive abilities.